2021
DOI: 10.4012/dmj.2020-381
|View full text |Cite
|
Sign up to set email alerts
|

Flexural properties and wear behavior of computer-aided design/computer-aided manufacturing resin blocks

Abstract: This study investigates the flexural properties, Knoop hardness number (KHN), and wear behavior of computer-aided design and computer-aided manufacturing (CAD/CAM) resin blocks and compares these values with those of conventional resin composites for direct restoration (RCDs). Four CAD/CAM resin blocks and two RCDs are compared. Ten specimens per material are used to obtain the flexural properties according to ISO 6872 specifications, and five specimens per material are used for KHN measurement. For sliding im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…2 Other researchers assumed that high wear resistance of the material could be attributed to the high content of filler particles with a fine size of 1 µm or less with less interparticle spacing, that may strengthen and protect matrix and reduce plucking of filler. 15,21,40,42,45,46 VITA Enamic and VITA Suprinity showed high wear resistance with no significant difference between them after chewing simulation agreeing with previous studies that showed less degradation of VITA Enamic compared to materials with a greater content of resin matrix. 47 VITA Enamic ceramics include 86% ceramic inorganic phase and 14% polymer organic phase and possessed features of both composites and ceramics, leading to sufficient flexibility, optimal distribution of chewing forces and high resistance to loads.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2 Other researchers assumed that high wear resistance of the material could be attributed to the high content of filler particles with a fine size of 1 µm or less with less interparticle spacing, that may strengthen and protect matrix and reduce plucking of filler. 15,21,40,42,45,46 VITA Enamic and VITA Suprinity showed high wear resistance with no significant difference between them after chewing simulation agreeing with previous studies that showed less degradation of VITA Enamic compared to materials with a greater content of resin matrix. 47 VITA Enamic ceramics include 86% ceramic inorganic phase and 14% polymer organic phase and possessed features of both composites and ceramics, leading to sufficient flexibility, optimal distribution of chewing forces and high resistance to loads.…”
Section: Discussionsupporting
confidence: 90%
“…20 On the other hand, CAD/CAM resin-based blocks represented in our research as Lava Ultimate can endure and absorb direct impact forces that result in increased wear resistance of opposing materials due the low modulus and the high resilience. 21 Since clinical wear analysis is too much problematic to be standardized, in-vitro wear tests are used for their rapid evaluation of wear properties of restorative materials such as the twobody wear, three-body wear, rotating sliding wear and toothbrush simulation as well as pin-on-plate test. Materials that reveal acceptable results can be further submitted to chewing simulation that can reproduce the physiological conditions such as the biting force, chewing movement and lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with light curing, high-temperature and high-pressure curing can prominently enhance the bending strength, Weibull modulus, hardness and density of resin [ 139 , 140 ]. At present, resin-based ceramic products cured at high temperature and high pressure have stronger mechanical properties [ 141 ]. This is because high temperature and high pressure can accelerate the molecular crosslinking reaction and shift the reaction equilibrium towards the positive direction [ 138 , 142 , 143 ].…”
Section: Ways To Reduce Biodegradationmentioning
confidence: 99%
“…If it is not controlled, however, wear can lead to reduced chewing ability, decreasing the quality of life and potentially deteriorating overall health [ 2 , 3 ]. Ideally, restorative materials should undergo wear in the same way as natural dentition [ 4 ]. While the literature describes many methods for assessing wear, advances in digital technology are now making the three dimensional (3D) measurement of progress the gold standard [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wear is mainly attributed to the particle size of the materials tested and the way the particles are packaged. In addition, the water absorption capacity and inorganic percentages of the materials also affect the wear patterns [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] ]. Determining the wear patterns of current restorative materials will prevent additional costs by reducing restoration renewals due to incorrect material selection; it will also result in more successful restorations.…”
Section: Introductionmentioning
confidence: 99%